2020
DOI: 10.1002/jor.24865
|View full text |Cite
|
Sign up to set email alerts
|

Trichostatin A regulates fibro/adipogenic progenitor adipogenesis epigenetically and reduces rotator cuff muscle fatty infiltration

Abstract: Rotator cuff (RC) muscle fatty infiltration (FI) is an important factor that determines the clinical outcome of patients with RC repair. There is no effective treatment for RC muscle FI at this time. The goal of this study is to define the role Trichostatin A (TSA), a histone deacetylase (HDAC) inhibitor in regulating muscle fibro/adipogenic progenitors (FAPs) adipogenesis and treating muscle fatty degeneration after massive RC tears in a mouse model. We hypothesize that TSA reduces muscle FI after massive RC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 49 publications
0
22
0
Order By: Relevance
“…The fibrosis and fat indices were quantified using ImageJ (NIH) by dividing the amount of collagen or lipids identified on Trichrome or Oil-red-O, respectively, by the total tissue section area (n = 3 to 4 mice/group/timepoint), as previously described [13] , [14] . Muscle fiber cross sectional area (CSA) was quantified using ImageJ (n = 3/group).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The fibrosis and fat indices were quantified using ImageJ (NIH) by dividing the amount of collagen or lipids identified on Trichrome or Oil-red-O, respectively, by the total tissue section area (n = 3 to 4 mice/group/timepoint), as previously described [13] , [14] . Muscle fiber cross sectional area (CSA) was quantified using ImageJ (n = 3/group).…”
Section: Methodsmentioning
confidence: 99%
“…At 6 and 15 weeks, muscle segments from bilateral proximal and distal muscle samples relative to disc injury were pooled (6 weeks: n = 4; 15 weeks n = 3) for flow cytometry isolation of Sca1 + /PDGFRα + /CD31 − /CD45 − /integrin α7 − FAPs as previously described [14] .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors explain that the functional purpose of FAPs is still under intense investigation; however, their presence in skeletal muscle pathology may indicate the presence of a resident stem cell population that could aid in muscle regeneration under the proper stimulus. One study found that HDACi treatment in a murine RCT model reduced FAP fibro-adipogenic activity while promoting differentiation into brown/beige adipose tissue (BAT), a metabolically active alternative to energy-storing white adipose tissue (62).…”
Section: Beige Adipose Tissue: a Latent Regenerative Phenotype Of Fapsmentioning
confidence: 99%